A dual-cathode photoelectrocatalysis-electroenzymatic catalysis system by coupling BiVO4 photoanode with hemin/Cu and carbon cloth cathodes for degradation of tetracycline. (1st March 2019) - Cheng, Ling; Jiang, Tao; Yan, Kai; Gong, Jianyu; Zhang, Jingdong
Abstract: When photoelectrocatalysis (PEC) couples with electroenzymatic catalysis (EEC), effective utilization of electrons from PEC process for yield of H2 O2 plays an important role in the enzymatic catalysis. In the present work, we designed a novel dual-cathode PEC-EEC system for pollutant removal. In this system, BiVO4 photoanode was prepared by electrodeposition for visible light-driven PEC process while carbon cloth was used as the first cathode for electrogeneration of H2 O2 and hemin/Cu prepared by electrophoretic deposition acted as the second cathode for enzymatic catalysis. The performances of the constructed dual-cathode PEC-EEC system were evaluated by decoloring Rhodamine B (RhB), which showed high decoloration percentage with acceptable stability and reusability. Further, the system was applied to degradation of tetracycline (TC), indicating that about 93.6% of TC was removed after 2-h treatment. A pathway for TC degradation in such a dual-cathode PEC-EEC system was proposed based on the intermediates determined by liquid chromatography coupled to mass spectrometry in tandem (LC-ESI-MS/MS). Graphical abstract: Highlights: A dual-cathode PEC-EEC coupling system is demonstrated for the first time. The system consists of a BiVO4 anode, a hemin/Cu cathode and a carbon cloth cathode. Synergistic decoloration of Rhodamine B by dual-cathode PEC-EEC is demonstrated. The dual-cathode PEC-EEC system is applied to degradation of tetracycline. A degradation pathway for tetracycline in dual-cathode PEC-EEC system is proposed.